Fatty acid composition, diosgenin and trigonelline contents of fenugreek (Trigonella foenum-graecum): effects of phosphorus fertilizer - Beyzi, Erman; Safak, Esra Kongul; Gurbuz, Perihan; Kosar, Muberra; Gurbuz, Bilal (Taylor & Francis Ltd, 2021)
The present study was conducted to investigate the effects of phosphorus fertilizer treatments (0, 30, 60, 90 and 120 kg ha(-1)P(2)O(5)) on crude oil, diosgenin, and trigonelline contents and on fatty acid composition of fenugreek plants. Experiments were conducted in a randomized block design with four replications. Results revealed under different phosphorus fertilizer doses that crude oil content varied between 4.75 and 5.54%, diosgenin content varied between 0.43 and 0.52% and trigonelline content varied between 0.74 and 0.97%. The highest diosgenin and trigonelline contents were obtained under the 30 kg ha(-1)P(2)O(5)treatment and the highest crude oil content was observed under the 60 kg ha(-1)P(2)O(5)treatment. With regard to fatty acid composition, C-18:2, C-18:3, C-16:0, C-18:0, C(18:1)and C(20:0)were identified as the major components and C-14:0, C-16:1, C-17:0, C-17:1, C(20:1)and C(22:0)were identified as the minor ones. Linoleic acid (C-18:2) content varied between 42.78 and 43.44% and linolenic acid (C-18:3) content varied between 26.77 and 29.21%. Except for linolenic acid (C-18:3), the highest contents of all the other major components were observed with the 90 kg ha(-1)P(2)O(5)treatment.
Keywords: Fenugreek; diosgenin; trigonelline; crude oil content; fatty acid composition; Trigonella foenum-graecum